ChemInform Abstract: A Dual Arylboronic Acid—Aminothiourea Catalytic System for the Asymmetric Intramolecular Hetero‐Michael Reaction of α, β‐Unsaturated Carboxylic Acids. Issue 8 (February 2015) - Azuma, Takumi; Murata, Akihiro; Kobayashi, Yusuke; Inokuma, Tsubasa; Takemoto, Yoshiji
Abstract For the first time aminoboronic acids (such as BNP) are used as efficient catalysts for the direct intramolecular hetero‐Michael addition to α, β‐unsaturated carboxylic acids to give a wide variety of O‐ and N‐containing heterocycles.